Dilatation and curettage versus lesion resection in the treatment of cesarean-scar-pregnancy: A systematic review and meta-analysis - Jiajia Li; Hongye Li; Jing Jiang; Xiaolin Zhang; Shuzhi Shan; Xin Zhao; Bin Shi (Elsevier, 2021)
This meta-analysis was performed to compare the efficacy and safety of dilatation and curettage (D&C) (simply D&C or combined with other treatments) and lesion resection for cesarean scar pregnancy (CSP). A search of English and Chinese databases from 2010 to 2019 was conducted. Thirty one studies were retrieved including sixteen random controlled and fifteen case controlled trials. Compared with abdominal resection surgery(ARS) and vaginal resection surgery(VRS), uterine artery embolization(UAE)+D&C has no obvious difference in curative effect and safety (UAE + D&C versus ARS: Cure rate(CR): P = 0.076, time for menstruation recovery/β-HCG normalization: P = 0.545/0.949,Blood loss: P = 0.005, adverse event: P = 0.420; versus VRS: CR: P = 0.085, time for menstruation recovery/β-HCG normalization: P < 0.001/P = 0.031,Blood loss: P = 0.902, adverse event: P = 0.249). UAE + D&C associated with lower blood loss and less postoperative complication than laparoscopic resection surgery(LRS), but LRS take more advantages in terms of the curative effect (CR: P = 0.047, time for menstruation recovery/β-HCG normalization: P = 0.352/0.103). The efficacy and safety of VRS are better than D&C, methotrexate (MTX) + D&C (D&C versus VRS: CR: P < 0.001, time for β-HCG normalization: P = 0.363,blood loss: P < 0.001, adverse event: P = 0.046; MTX + D&C versus VRS: CR: P < 0.001, time for menstruation recovery/β-HCG normalization: P < 0.001/P = 0.005, blood loss: P < 0.001, adverse event: P < 0.001). Lesion resection had advantages in shorter time for menstrual recovery/β-HCG normalization and less adverse events, lower failure rate over the administration of D&C treatments. In detail, the curative effect of UAE + D&C is similar to ARS and VRS, but inferior to LRS, while the safety of UAE + D&C is better than LRS. The efficacy and safety of simply D&C and MTX + D&C are not as good as VRS.